PENGARUH SUBSTITUSI EKSTRAK RUMPUT LAUT COKLAT TERHADAP KUALITAS PERMEN JELI - Zuhri, Rezmia; Faridah, Anni; Holinesti, Rahmi (Journal of Home Economics and Tourism, 2017)
This research was based on the utilization of sargassum sp. Sargassumsp is still a wastealong the edge of Nirwana beach. This study aimed to analyze the effect of substitution ofsargassumsp extract as much as 20%, 30%, and 40% to the quality of jellycandy in terms ofshape, color, smell, texture and taste. This research type was true experiment with doublerandom method. Types of data were primary data sourced from 30 panelists by filling theorganoleptic test format to the sample. The data were analyzed by Variant Analysis ifFcount>Ftableandwas continued by Duncan test. The results showedthat the amount ofbrown seaweed extract use affected the quality of the clear brown color, the smell of brownseaweed, and chewy texture. Overall,the highest scores were shape (rectangle) 3.62 (30%),shape (tidy) 3,59 (40%), shape (match) 3.64 (30% and 40%), color (brownish nodes ) 3.78(40%), color (white) 3.12 (20%, 30% and 40%), smell (sugar) 3,50 (20%), smell (brownseaweed) 1,81 (40 %), Texture (chewy) 3.58 (40%), and flavor (sweet) 3.31 (20%). The bestquality result of brown seaweed extract was 40%.Keywords: Sargassumsp, Jelly Candy, Quality.